1990
DOI: 10.1159/000107119
|View full text |Cite
|
Sign up to set email alerts
|

Galanthamine Hydrobromide in a Long-Term Treatment of Alzheimer's Disease

Abstract: We investigated the long-term administration of galanthamine hydrobromide, a cholinesterase inhibitor, in Alzheimer''s disease. The patient was at an advanced stage of the disease and remained unchanged with respect to the results of psychometrical tests. The clinical global impression, however, improved with dosage, and clinical improvement was associated with a remarkable and selective inhibition of acetylcholinesterase activity. Galanthamine was well tolerated without adverse effects or pathological changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Thus, GAL has been shown to be competitive with other anticholinesterastic compounds like tacrine or physostigmine in the treatment of the syndrome (Rainer et al, 1989). In contrast with the proven hepatotoxicity of tacrine (Gauthier et al, 1990), GAL shows minor effects like agitation or insomnia (Thomsen et al, 1990), with only moderate acute toxicity (Antonyan et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, GAL has been shown to be competitive with other anticholinesterastic compounds like tacrine or physostigmine in the treatment of the syndrome (Rainer et al, 1989). In contrast with the proven hepatotoxicity of tacrine (Gauthier et al, 1990), GAL shows minor effects like agitation or insomnia (Thomsen et al, 1990), with only moderate acute toxicity (Antonyan et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…As THA has a significant side-effect profile, particularly in terms of hepatotoxicity and unwanted peripheral cholinergic activity, we have investigated, in an open pilot study, galanthamine hydro-bromide, an anticholinesterase alkaloid derived from the common snowdrop. There have been a small number of previous studies (eg Rainer et al, 1989;Thomsen et al, 1990;Dal Bianco et al, 1991) which in general reported minor degrees of benefit, although statistically insignificant. As these earlier studies used widely varying doses, we have assessed the therapeutic efficacy and tolerance of a low dose, 30-40 mg/day, against a higher dose, 45-60 mg/day, in patients suffering with probable Alzheimer's disease according to the NINCDS criteria (McKhann et al, 1984).…”
Section: Dear Editormentioning
confidence: 94%
“…The bromo-tritium exchange took place in tetrahydrofuran using a palladium catalyst poisoned with butanethiol in order to avoid a possible reduction of the allylic double bond. HPLC purification and resolution produced tritium-labelled galantamine (6). Recently, a procedure was described to obtain 1-bromogalantamine directly from galantamine, 35 which would avoid the final resolution step.…”
Section: Tritium-labelled Galantaminementioning
confidence: 99%
“…from various species of Narcissus. 3,4 Galantamine shows reversible, competitive acetylcholinesterase inhibiting and nicotinic acetylcholinergic receptor modulatory properties [5][6][7] and readily crosses the blood-brain barrier. It is generally accepted that cognitive and functional improvement can be achieved with compounds that increase cholinergic neurotransmission in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%